Pengaruh Persepsi Risiko dan Kepercayaan Terhadap Minat Beli Konsumen E-Commerce Blibli.com di Sidoarjo - Dewi Fathika Sari; Rizky Dermawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research intends to ascertain how perceived risk and trust affect Sidoarjo users of the Blibli.com e-commerce site's desire to make a transaction. Purposive sampling is a form of quantitative methodology that was utilized in this investigation. 104 respondents make up the study sample. Users who reside in Sidoarjo and Blibli.com e-commerce users were given questionnaires as part of this research's data collection. The answers of the questionnaire have been deemed valid and trustworthy, and the Partial Least Square (PLS) model was utilized as the study's analytical tool. The findings of this research show that perceived risk has a positive and large impact on the purchase intentions of Blibli.com e-commerce customers, and trust has a positive and significant impact as well. Constructive suggestions that can be considered in buying interest are that Blibli.com needs to focus on providing clear price information, price comparison features with competitors, special program discounts, lowest price guarantees, and loyalty programs to reduce consumer risk perceptions. In addition, Blibli.com must improve customer service, personalized experience, delivery process, transparency, product quality, ease of return, and e-commerce technology innovation to create sustainable trust in providing satisfaction to customers. Future research can consider other variable factors that can influence purchase intention so that research results become more comprehensive and better. Keywords: Purchase Intention, Perceived risk, Trust.